1989
DOI: 10.2105/ajph.79.11.1521
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of childhood injuries: evaluation of the Statewide Childhood Injury Prevention Program (SCIPP).

Abstract: We evaluated the effectiveness of a community-based injury prevention program designed to reduce the incidence ofburns, falls in the home, motor vehicle occupant injuries, and poisonings and suffocations among children ages 0-5 years. Between September 1980 and June 1982, we implemented five injury prevention projects concurrently in nine Massachusetts cities and town; five sites, matched on selected demographic characteristics, were controlcommunities. An estimated 42 percent of households with children ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 19 publications
0
55
0
1
Order By: Relevance
“…These included a CBA evaluating a community injury prevention programme (OR 0.95, 95% CI 0.57À1.58 (Guyer et al, 1989)), one NRCT evaluating poison prevention education (IRR 0.98, 95% CI 0.45À2.13 (Fergusson, Horwood, Beautrais, & Shannon, 1982)), one NRCT evaluating safety education and safety equipment provision covering In unpaid work…”
Section: Interventions To Prevent Poisoning-related Injuriesmentioning
confidence: 99%
“…These included a CBA evaluating a community injury prevention programme (OR 0.95, 95% CI 0.57À1.58 (Guyer et al, 1989)), one NRCT evaluating poison prevention education (IRR 0.98, 95% CI 0.45À2.13 (Fergusson, Horwood, Beautrais, & Shannon, 1982)), one NRCT evaluating safety education and safety equipment provision covering In unpaid work…”
Section: Interventions To Prevent Poisoning-related Injuriesmentioning
confidence: 99%
“…11,16 Additional study is needed to learn the best injury prevention methods for use with low-income families. Counseling may be more effective when it is associated with more concrete measures like environmental modification.…”
Section: Discussionmentioning
confidence: 99%
“…Eligible interventions were coordinated, multi-strategy initiatives, and controlled community trials were included that reported changes in medically attended injuries. Of 32 studies, 3 met criteria for inclusion (Guyer et al, 1989;MacKay & Rothman, 1982;Ytterstad, Smith, & Coggan, 1998;Ytterstad & Sogaard, 1995). Project Burn Prevention was an educational campaign delivered through mass media, schools, and community organizations and was implemented in two Boston communities from October 1977 to May 1978(MacKay & Rothman, 1982.…”
Section: Community-based Campaigns (Insuffi Cient Evidence) a Recentmentioning
confidence: 99%
“…The Massachusetts Statewide Childhood Injury Prevention Program (SCIPP) was an injury prevention educational intervention, with burn prevention being one of fi ve target project areas; it was implemented in nine cities between September 1980 and June 1982. SCIPP implemented the Project Burn Prevention curricula through schools, libraries, police and fi re authorities, and day-care facilities (Guyer et al, 1989). The Harstad Injury Prevention Study used the Safe Communities method and targeted burns and scalds in children younger than 5 years of age.…”
Section: Community-based Campaigns (Insuffi Cient Evidence) a Recentmentioning
confidence: 99%
See 1 more Smart Citation